A new species of Hyphessobrycon Durbin (Characiformes: Characidae) from rio Aripuanã, rio Madeira basin, Brazil - Pastana, Murilo N. L.; Ohara, Willian M. (Zootaxa, 2016)
A new species of Hyphessobrycon is described from the rio Aripuanã, rio Madeira basin, Amazonas State, Brazil. Hyphessobrycon procyon can be distinguished from its congeners by the unique combination of the following features: elongation of the dorsal fin in mature males, absence of dark blotches on the dorsal fin, and presence of two humeral blotches. The possibility of a relationship of the new species within H. elachys, H. heliacus, H. loweae, H. moniliger, and H. peugeoti is discussed based on the sharing of characteristics related to the sexual dimorphism and tooth morphology.